UMKM Digital Upaya Agar Bisnis Bisa Terus Berjalan - Julius F Nagel; Ninuk Muljani (FEB Universitas Sultan Ageng Tirtayasa, 2022)
World Bank: MSMEs Most Affected by the Covid 19 Pandemic. In order for MSMEs to transform, it is necessary to integrate government assistance and assistance with the digital ecosystem. Three extraordinary ideas for national economic recovery. A number of local governments have provided stimulus to help micro, small and medium enterprises to rise from adversity due to the Covid-19 pandemic. MSMEs are the driving force of the economy, there must be strategies and policies to develop MSMEs. Business challenges for MSMEs during the pandemic: it is difficult to expand, and company finances are disrupted. To overcome this problem, business people can implement a number of strategies so that the business can run smoothly, namely ensuring a healthy cash flow. The Ministry of Cooperatives has four pillar policies to help MSMEs go digital faster: modern cooperative policies, ease of business licenses, strategy development and business incubation to increase the support capacity of MSME development. The government has provided a stimulus for MSMEs in the form of subsidized interest assistance, credit restructuring and tax incentives. There are 4 advantages of digitizing MSMEs: financial benefits through increased sales, opportunity creation, benefits for buyers with the opportunity to earn 11-25% of retail prices, and social cooperation. Some tips so that MSMEs can survive in the midst of the corona virus: focus on consumer needs, keep going and be creative, develop research and development to increase resilience when the crisis hits, MSMEs will not be complacent because the competition will be tougher, prepare the next one to become a leader MSMEs of the future, maintain good reciprocal relationships with vendors, suppliers and distributors, join MSME organizations as a means of network and business development, collaborate with banks as strategic partners for financing sources. As a conclusion, solving MSME problems does not open their hands, but with serious, collective and integrated efforts, and never give up from the government together with BI, financial services authorities and MSME actors themselves.